Shuffling through the Bargain Bin: Real-Estate Holdings of Public Firms - Demirci, Irem; Gurun, Umit G; Yönder, Erkan (Review of Finance, 2020)
Abstract Constructing a novel database on the real-estate holdings of public firms, we show that distressed firms sell their real-estate assets at a discount relative to healthy firms. We find that distress discount in real-estate assets is less pronounced for sellers with less liquidity-constrained industry peers and in machinery-heavy industries. We also document that asset redeployability and the availability of potential buyers are two important property-specific determinants of the distress discount. Additionally, firms’ property portfolios that are less redeployable with less potential buyers exacerbate the negative impact of financial distress on the cost of borrowing.